Towards Decolonial Praxes in Critical Peace Education for Sustainable Futures - Sulyman, Abdulganiy; Ukwumaka, Kate (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2024)
This paper examines decolonial praxes in critical peace education using philosophical framework of African Conversational School. In the process, it examines: Conversational School of African Philosophy, critical peace education for sustainable futures, the importance of decolonial praxes, conceptual framework for critical peace education for sustainable future, Nigerian educational system and education policies of Federal Republic of Nigeria (FRN), Economic Community of West African States (ECOWAS) and African Union (AU). The paper theorizes that decolonial praxes in critical peace education should be pursued with a combination of local and global cultures (glocalization) for sustainable futures since both cultures have positive contributions to human life. Therefore, the conclusion and suggestions of this paper are partly based on this theoretical position. Introduction of decolonial critical peace education as a separate subject and as objectives in other subjects is the main suggestion and conclusion made.